Cell phone networks and migrant networks: The case of Nayu migrant workers in Malaysia - Bunmak, ﻿Suttiporn (Faculty of Social Sciences and Humanities, UKM,Bangi, 2012)
﻿To be able to communicate as and when one wants to is to be empowered. The increasing use of cell phones has indeed become a significant part of the everyday life for migrant workers. The cell phones which already play such a vital role in enhancing migrant workers’ geographical mobility are now used for connection and to maintain social contacts.This paper examines the relationship between cell phone networks and the social networks amongThailand’s migrant Nayu workers and finds that the cell phone is used by them to maintain and reinforce existing networks and to create new social ties among fellow workers. The cell phone enables the migrant workers to stay connected at all time to their networks whether they are absent from home, at work or crossing the border both in Thailand and Malaysia.